The impact of time to surgery after hip fracture on mortality at 30- and 90-days: Does a single benchmark apply to all?. Issue 4 (April 2019) - Beaupre, L.A.; Khong, H.; Smith, C.; Kang, S.; Evens, L.; Jaiswal, P.K.; Powell, J.N.
Highlights: Mortality within 30- and 90-days of hip fracture increased significantly with increasing time to surgery and increasing age. Time to surgery after hip fracture may differentially affect survival with older patients more affected by surgical delay than younger patients. Males and those with a higher comorbid burden also had higher odds of dying after controlling for time to surgery. A single benchmark for time to surgery may not be appropriate; stratifying mortality risk based on patient characteristics should be considered. Abstract: Introduction: Delays to surgery after hip fracture have been associated with mortality Uncertainty remains as to what timing benchmark should be utilized as a marker of quality of care and how other patient factors might also influence the impact of time to surgery on mortality. The goal of this study was to determine how time to surgery affects 30- and 90-day mortality by age and to explore the impact of preoperative comorbid burden and sex. Participants: We used population-based administrative data from a Canadian province collected from 01April2008 to 31March2015. Of 12, 713 Albertans 50-years and older who experienced a hip fracture and underwent surgery within 100 h of admission, 11, 996 (94.8%) provided data. Methods: Time to surgery was analyzed in hours from admission to surgery. Age and the interaction between age and time to surgery were evaluated using logistic regression. Charlson co-morbidity score and sex were also considered in the analysis. Survival was evaluated at 30-and 90-days post hip fracture using a provincial registry. Results: The average age of the cohort was 79.6 ± 11.2 years and 8, 412 (70.1%) were female. Overall, 586 (4.9%) patients died within 30-days and 1, 023 (8.5%) died within 90-days of hip fracture. Mortality increased significantly with increasing time to surgery (30-day mortality odds ratio [OR] = 1.03; 95%CI 1.01-1.05: 90-day mortality OR = 1.03; 95% CI 1.01–1.04). Mortality also increased substantially with increasing age; those ≥85 years were 19.63 (95% CI 6.83–67.33) and 15.66 (95%CI 7.20–37.16) times the odds more likely to die relative to those between 50–64 years of age at 30-days and 90-days postoperatively respectively. Further, those who were ≥85 years were more significantly affected by increasing time to surgery than those who were 50–64 years of age at both 30-days (p = 0.04) and 90-days (p = 0.025) post-fracture. Males and those with a higher comorbid burden also had higher odds of dying after controlling for time to surgery (p < 0.001) Conclusion: Time to surgery following hip fracture may have a differential effect on 30- and 90-day survival dependent on age. Older patients appear to be at higher risk of dying with surgical delays than younger patients.